In situ observation of ocean response to tropical cyclone in the western North Pacific during 2022 - He, Hailun; Ling, Zheng; Wu, Shouchang; Lyu, Xinyan; Zeng, Zheng; Tian, Ruizhen; Wang, Yuan; Sun, Jia (Frontiers in Marine Science, 2024)
We deployed 8 surface drifters in the western North Pacific in 2022. By integrating the Global Drifter Program's data, we analyzed the drifter-based sea surface currents and temperatures during tropical cyclones. The maximum in-situ surface current observed was 0.70 m/s during typhoon Hinnamnor. Our surface drifters provided similar observations as compared to an adjacent Global Drifter Program's drifter. Furthermore, we investigated float profiling observations during tropical cyclones. Based on Argo float 2903647, the SST decreased by 1.4oC after the passage of typhoon Hinnamnor. This study demonstrates the reliability of our newly deployed surface drifters and exhibits the state-of-the-art capability for in-situ observations of tropical cyclone-ocean interaction.